NiCoFe oxide amorphous nanohetrostructres for oxygen evolution reaction. (30th August 2019) - Sial, Muhammad Aurang Zeb Gul; Baskaran, Sambath; Jalil, Abdul; Talib, Shamraiz Hussain; Lin, Haifeng; Yao, Yuechao; Zhang, Qi; Qian, Haixia; Zou, Jizhao; Zeng, Xierong
Abstract: Two dimensional (2D) nanohetrostructures (NHS) composed of multimetal oxide nanoparticles (NPs) with site selective growth on either basal or lateral of the 2D multimetal oxide nanosheets (NSs) substrate are highly desirable due to their unique chemical and physical properties but extremely challenging in preparation. Herein, for the first time, we demonstrate the rational control growth of amorphous NiCoFeOx NPs on either lateral or basal of amorphous NiCoFeOx NSs by hydrothermal method. Owing to the lateral growth of amorphous NiCoFeOx NPs on the amorphous NiCoFeOx NSs, this unique architecture exhibits more electrocatalytic active sites and better stability due to higher In-plane conductivity than interlayer conductivity. Furthermore, density functional theory (DFT) calculation shows that due to the presence of low coordinated oxygen, it decreased the energy barrier of intermediates and enhanced the oxygen evolution reaction (OER) performance. While, NiCoFe oxide NHS with lateral growth of NiCoFeOx NPs lead to superior electrocatalytic activity toward oxygen evolution reaction (OER) with a low overpotential of 232 mV to reach a current density of 10 mAcm −2, due to the amorphous nature of NHS, synergistic effect, conductive support (like Nickel Foam) with metal oxide substrate. Furthermore, employing Lateral growth NHS as an anode and cathode for water splitting electrolyzer able to reach 10 mAcm −2 at a cell voltage of 1.49 V with robust durability. This work will provide a new dimension for the construction of other site selective 2D NHS with unique properties especially for OER. Graphical abstract: Two dimensional (2D) nanohetrostructures (NHS) composed of multimetal oxide nanoparticles (NPs) with site selective growth was prepared that lead to superior electrocatalytic activitytoward overall water splitting.Image 1 Highlights: Amorphous Nanohetrostructure (NHS) with site selective growth was synthesized. Lateral growth NiCoFe oxide NHS lead to superior electrocatalytic activity. DFT calculation shows that high activity due to presence of low coordinated oxygen.